A chain is no stronger than its weakest link: Weathering resistance of water-based intumescent coatings for steel applications. (January 2021) - Daus, Lars-Hendrik; Schartel, Bernhard; Wachtendorf, Volker; Mangelsdorf, Rolf; Korzen, Manfred
A systematic approach was used to investigate the weathering-induced degradation of a common water–based intumescent coating. In this study, the coatings are intended for humid indoor applications on steel substrates. The coating contains ammonium polyphosphate, pentaerythritol, melamine, and polyvinyl acetate. By replacing each ingredient with a less water-soluble substance, the most vulnerable substances, polyvinyl acetate and pentaerythritol, were identified. Furthermore, the weathering resistance of the system was improved by exchanging the ingredients. The coatings were stressed by artificial weathering tests and evaluated by fire tests. Thermogravimetry and Fourier-transform infrared spectroscopy were used to study the thermal decomposition. This study lays the foundation for the development of a new generation of water-based intumescent coatings.